Hegemonic masculinity, education, and work: an intersectional analysis of high school students' conceptions - Henrique, Eduardo dos Santos (2024)
This article aims to analyze, through an intersectional lens (Collins, 2020), the interweaving of hegemonic masculinity conceptions with expectations of productivity and economic success in interactions with high school students at a public school in southern Santa Catarina. The study employed an action-research method (Baldissera, 2001) for data collection, which took place during Portuguese language classes focused on gender and sexuality as part of a specialized high school track. Classroom discussions revealed that hegemonic masculinity benefits a cis-heteronormative, white male elite, reinforcing stereotypes that link masculinity to the responsibility of work. Additionally, students expressed critical perspectives on masculinities, challenging these stereotypes and exploring alternative forms of male identity. Finally, the school is seen as a space that can encourage reflective dialogues on gender and sexuality, working to dismantle power structures and promote a more equitable and democratic education.